2023
DOI: 10.3390/atmos14040697
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Wind Speed Forecasting Based on the EEMD-GS-GRU Model

Abstract: To improve the accuracy of short-term wind speed forecasting, we proposed a Gated Recurrent Unit network forecasting method, based on ensemble empirical mode decomposition and a Grid Search Cross Validation parameter optimization algorithm. In this study, first, in the process of decomposing, the set empirical mode of decomposition was introduced to divide the wind time series into high-frequency modal, low-frequency modal, and trend modal, using the Pearson correlation coefficient. Second, during parameter op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, the decomposition method has shown that through the decomposition process, each subsequence of the original signal can reveal the signal's distinct intrinsic features and obtain more features for the predicted signals. The empirical mode decomposition (EMD) technique has widely been used for decomposing original signals into their intrinsic multiscale features [21]. Tan [22] and Elias [23] each proposed a prediction model combining the EEMD method and the ML algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the decomposition method has shown that through the decomposition process, each subsequence of the original signal can reveal the signal's distinct intrinsic features and obtain more features for the predicted signals. The empirical mode decomposition (EMD) technique has widely been used for decomposing original signals into their intrinsic multiscale features [21]. Tan [22] and Elias [23] each proposed a prediction model combining the EEMD method and the ML algorithms.…”
Section: Introductionmentioning
confidence: 99%